E-Cigarette as Distruptive Innovation: Forecasting of conventional cigarette substitution in Indonesia - Erman Aminullah (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2019)
This paper intends to forecast conventional cigarette substitution by e-cigarette in the context of disruptive innovation. E-cigarette as disruptive innovation has been driven by technology innovation to create e-cigarette products for global market. The advancement of e-cigarette technology innovation would continue to create smart and less harmfull e-cigarette as alternative tobacco products in future.The results of forecasting show that the replacement of conventional cigarette would be in line with the increase of e-cigarette consumption. The future increase of e-cigarette consumption would be influenced by three factors: (i) technology advancement, (ii) excise tax incentives, (iii) and tobacco regulation. The diffusion of e-cigarette products in domestic market have raised the level of public acceptance, despite still reaped some rejections, especially from the health community in Indonesia. The scientific contribution of paper is a system dynamics model on conventional cigarette substitution by e-cigarette’s disruptive innovation. The model is systemic interaction among cigarette consumption, regulators, and public responses both health community and consumers of e-cigarette in Indonesia. Keywords: disruptive innovation, product substitution, electric-cigarette, system perspective, forecasting.